The Elevated BMI is Considerably Associated with IDD Rather than Polymorphic variations in Interleukin-1 and Vitamin D Receptor Genes: A Case-Control Study: BMI and IDD - Al Zoubi, Mazhar Salim (Journal of Medical Biochemistry, 2020)
Intervertebral disc degeneration (IDD) is a musculoskeletal disorder and one of the major causes of low back pain leading to the disability with high economic repercussions worldwide. This study applied the candidate-gene approach to investigate the potential association of selected polymorphisms with IDD development in a Jordanian population. MRI-diagnosed IDD patients (N=155) and asymptomatic individuals as a control group (N=55). Whole blood samples for four variants in three genes (rs1800587 of IL-1α, rs1143634 of IL-1b and rs2228570 and rs731236 of VDR) were genotyped by PCR-RFLP. There was no significant association between the studied polymorphisms or their allelic frequency and the occurrence of IDD. However, the cohort presented a significant reverse association between rs1143634 C>T of the IL-1β gene and the occurrence of IDD (p< 0.0001). In addition; BMI showed a significant association with the IDD in the study population (p< 0.005). The current study was conceptualized based on the candidate-gene approach to investigate the role of inflammatory and metabolic genes, IL and VDR respectively, in the occurrence of IDD. While data presented in this study showed that polymorphisms in these genes were not associated with IDD of the cohort investigated, elevated BMI, as a measure of obesity strongly associated with IDD. Investigating potential roles of other structural genes, such as col-IX and aggrecan (ACAN), in IDD and considering a GWAS to elucidate a genomically global look at the basis of IDD development would be of considerable impact on our understanding of IDD.
Keywords: BMI; IDD; Vitamin D Receptor; IL-1; SNP